KONSEP NARATOLOGI DALAM HIKAYAT PAK BELALANG: KAJIAN SASTRA BANDING - Febriyanti Tri Wahyuningtyas; Asep Yudha Wirajaya (Sunan Kalijaga State Islamic University Yogyakarta, 2024)
This study compared narrative elements in Pak Belalang texts in the form of hikayat and folklore. The purpose of this research was to find out the narrative form between two literary works based on the time of publication but sourced from the same text. This research can contribute to modern philology to know the history of text development. In this case, text variations are considered creations. The problem focused on the difference in the description of Pak Belalang's story through the past view in the form of hikayat as well as the modern view through a simplified folklore book. The comparative literature method was used to relate the differences and similarities between the texts. The elements were summarized using narratology theory to facilitate research. Hikayat and folklore were the main data for the comparative study. The research sources were Hikayat Pak Belalang and Cerita Rakyat Pak Belalang. The narratology theory examines the problem in five main points of discussion, namely: 1) order, 2) duration, 3) frequency, 4) moods, and 5) voices. Through these five elements, similarities were found in moods and voices. Meanwhile, differences were found in the elements of order, duration, and frequency.